The Influence of Corporate Social Responsibility and Business Ethics on Brand Fidelity: The Importance of Brand Love and Brand Attitude - Quezado, Tarcia Camily Cavalcante (2022)
Corporate social responsibility (CSR) and business ethics are perceived as distinct constructs by the consumer, although research from this perspective is scarce. Thus, the objective of this study is to investigate the impact of CSR and business ethics on brand fidelity. A theoretical review of CSR, business ethics, brand attitude, brand love, and brand fidelity was undertaken. From these constructs, a theoretical model was proposed, conducting an empirical study with a sample of 559 North American respondents. Through the statistical treatment of data with PLS-SEM, it was demonstrated that business ethics and CSR exert an indirect positive effect on brand fidelity, with relationships mediated by brand love. In turn, brand attitude exerts an indirect effect on brand fidelity, through the mediation of brand love. Based on the results, this study contributes to the approach of CSR and business ethics as distinct constructs and to the consolidation of the brand fidelity construct and its relationships. For management, this study helps organizations to perceive CSR and business ethics as important allies in a brand’s strategy. We conclude that although CSR remains important, customers value business ethics as a critical factor in their perceptions of the brand, contributing more strongly to brand fidelity.